Differential Foreign Body Reactions between Branched and Linear Glucomannan Scaffolds - Yuwei Li; Yu Liu; Senio Campos de Souza; Tzuwei Chao; Lei Dong; Guoxing Sun; Chunming Wang; Yiming Niu (Journal of Functional Biomaterials, 2022)
The extent and patterns of foreign body reaction (FBR) influence the function and feasibility of biomaterials. Polysaccharides, as an important biomaterial category, have received increasing attention in diverse biomaterials design and biomedical applications due to their excellent polymeric and biocompatible characteristics. Their biological effects are usually associated with their monosaccharide composition or functional groups, yet the contribution of their glycan structure is still unknown. Herein, two glucomannans, similar in composition and molecular weight with differences in glycan structure, linear-chain (Konjac glucomannan, KGM), and branched-chain (Bletilla striata polysaccharide, BSP), were adopted to explore the host–biomaterials interaction. After acetyl modification, these polysaccharides were fabricated into electrospun scaffolds to reduce the impacts derived from the physical properties and surface morphology. According to a systematic study of their biological effects on immune cells and host response in a subcutaneous implantation model in vivo, it was revealed that acetyl KGM (acKGM) scaffolds caused a stronger FBR than acetyl BSP materials. Additionally, acKGM could stimulate macrophages to release pro-inflammatory cytokines, suggesting the influence of sugar chain arrangement on FBR and providing clues for the fine regulation of immune response and novel biomaterials design.